Efficiency of Dry Formulation Bacillus sp. Ks5 to Plant Growth Promotion and Biological Control of Xanthomonas oryzae pv. oryzae Caused Bacterial Leaf Blight Disease - Buachard, Suwichaya; Phuangphee, Praphaphorn; Jamsai, Natthawan (YRU Journal of Science and Technology, 2022)
Screening of antagonistic bacteria from rhizosphere soil of rice. Antagonistic bacteria were isolated of 23 isolates. 6 isolates showed the efficiency to inhibit of bacterial blight of rice caused by Xanthomonas oryzae pv. oryzae. Bacillus sp. Ks5 indicad a difference higher inhibition of Xanthomonas oryzae pv. oryzae with clear zone 1.43 cm, using agar diffusion technique. Bacillus sp. Ks5 was adapted to the development of dry formulation and remarkably, this was successful as a carrier to maintain bacterial survival with 6.36×108 CFU/ml. The formulation from Bacillus sp. Ks5 was the most effective in inhibit bacteria pathogen that had been stored for 3 months with 2.20 cm, respectively. Dry formulation of Bacillus sp. Ks5 was able to produce plant growth promoters as ammonia.